Strategic Focus and Business Process Development for Profitability Enhancement in Case Company X : A Case Study - Niemi, Timo (My University, 2026)
This study examines what factors influence strategic focus as well as business processes and how these processes can be developed and optimized. Strategy and process development have often been studied based on individual management theories. The aim of this study was to combine several management theories into a holistic conceptual theoretical framework to produce a comprehensive research result. The purpose of this study is to reflect how Case Company X can define a clearer strategic focus for itself and develop and optimize its business processes to improve profitability and service efficiency. This study has been conducted as a qualitative case study to study three independent business areas of a small to medium-sized (SME) company. The primary research data has been collected using a semi-structured interview method from eight company managers as well as the company's CEO, there were conducted in total nine interviews. Secondary data for this study were collected from the company internal sources such as documentation management system and enterprise resource planning system. The research data was collected using two methods and this collected data was analyzed using thematic analysis. The data was coded based on a theoretical framework, on which the interview questions were also based. The results of this study show that there are many contributing factors to strategic focus and this was case-specific in the studied case company, which are the decisive factors for creating competitive advantage and which isolation mechanisms improve competitive advantage, creating VRIN-O resources that can create sustainable competitive advantage for the company in their business environment. The research results also showed that if the VRIN-O resources are not strong enough, the strategy and strategic focus have effect on the company's profitability and service efficiency. As the results showed, in this case, the company must support and develop these important resources by improving dynamic capabilities, exploit collaboration, and focus on value-generating activities to improve and extend its own resources to improve profitability as well as service efficiency. In terms of business processes, it could be observed that the maturity level of case company processes was weak and the processes were employee-dependent and operations were reactive. Based on these findings in business processes, clear areas for development opportunities were identified, which became evident from empirical research of the study. Based on these findings, it was possible to present initiatives for case company to develop and optimize business processes to improve their profitability and service efficiency.

Tämä tutkimus tarkastelee mitkä tekijät vaikuttavat strategiseen painopisteeseen sekä liiketoimintaprosesseihin ja miten näitä prosesseja voidaan kehittää ja optimoida. Strategiaa ja prosessien kehitystä on tutkittu usein yksittäisten johtamisteorioiden pohjalta. Tässä tutkimuksessa haluttiin yhdistää useampi johtamisteoria kokonaisvaltaiseksi käsitteelliseksi teoreettiseksi viitekehykseksi, jotta voitaisiin tuottaa kokonaisvaltainen tutkimustulos. Tämän tutkimuksen tarkoituksena on vastata miten tapausyritys X voi määrittää itselleen selkeämmän strategisen painopisteen ja kehittää ja optimoida liiketoimintaprosessejaan kannattavuuden ja palvelun tehokkuuden parantamiseksi. Tämä tutkimus on toteutettu laadullisena tapaustutkimuksena, jossa tarkastellaan pienen ja keskisuuren (PK) yrityksen kolmea itsenäistä liiketoiminta-aluetta. Ensisijainen tutkimusaineisto on kerätty puolistrukturoitua haastattelu menetelmää käyttäen kahdeksalta yrityksen päälliköltä sekä yrityksen toimitusjohtajalta, haastatteluja toteutettiin yhteensä yhdeksän tietojen keräämistä varten. Toissijainen data tätä tutkimusta varten kerättiin yrityksen sisäisistä lähteistä dokumentaationhallintajärjestelmästä sekä toiminnanohjausjärjestelmästä. Datan kerättiin kahdella menetelmällä ja tämä kerätty data analysoitiin temaattisen analyysin avulla. Data koodattiin teoreettiseen viitekehykseen pohjautuen, johon myös haastattelukysymykset pohjautuivat. Tämän tutkimuksen tulokset osoittavat, että strategisen painopisteeseen on monta vaikuttavaa tekijää ja tämä on tapauskohtaista tapausyrityksessä, mitkä ovat ratkaisevat tekijät kilpailuedun luomiseksi sekä mitkä eristäytymismekanismit parantavat kilpailuetua luoden yritykselle VRIN-O resursseja, jotka voivat luoda yritykselle kestävää kilpailullista etua toimintaympäristössä. Tutkimustulokset osoittivat myös, mikäli VRIN-O resurssit eivät ole riittävän vahvoja on strategialla ja strategisella painopisteellä on merkitystä yrityksen kannattavuuteen ja palvelun tehokkuuteen. Kuten tulokset osoittivat, tällöin tapausyrityksen on tuettava ja kehitettävä näitä tärkeitä resursseja parantamalla dynaamisia kyvykkyyksiä, hyödyntää yhteistyötä ja keskittyä arvoa tuottaviin toimintoihin parantaakseen ja laajentaakseen omia resurssejaan parantaakseen kannattavuuttaan sekä palvelun tehokkuutta. Liiketoimintaprosessien osalta voitiin havaita, että tapausyrityksen prosessien kypsyysaste oli heikko ja prosessit ovat työntekijäriippuvaisia ja operatiiviset toiminnot reaktiivisia. Prosessien osalta havaittiin myös selkeitä kehityskohteita, jotka tulivat ilmi tutkimuksen empiirisen tutkimuksen pohjalta. Näiden havaintojen perusteella pystyttiin esittämään tapausyritykselle vaihtoehtoja liiketoimintaprosessien kehittämiseen ja optimointiin sopivia toimia niiden kannattavuuden ja palvelun tehokkuuden parantamiseksi.
Keywords: fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master’s Programme in Industrial Engineering and Management